The European Union’s Post Brexit Agenda and Priority in Defense-Security Sectors - Wicaksono, Bayu; Nugrahani, Henny Saptatia Drajati (Journal of Strategic and Global Studies, 2023)
ABSTRACT This research aims to explore the European Union’s agenda and priority in defence and security sectors in post Brexit era. This study is analyzed based on two research questions are: first, what are the impacts of Brexit on the European Union (EU) defense-security sectors, and the second is, what are the EU’s agenda and priority in defense-security sectors in the Post-Brexit era. The method of this research is descriptive qualitative. The analyses of the study is using Barry Buzan and Ole Waever's Regional Security Complex Theory (RSCT). The findings of this study are: first, as the impact of Brexit, EU significantly prepare itself with many kinds of initiatives, policies and agreements in defense-security sectors. Second, EU has been establishing various scales and sachems of its agenda and priority in defense-security sectors in the Post-Brexit. Keywords: Post-Brexit era, EU’s agenda and priority, defense-security sectors, Regional Security Complex Theory (RSCT)